2011
DOI: 10.1182/asheducation-2011.1.556
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulating Drugs in Myelodysplastic Syndromes

Abstract: Based on immune mechanisms that appear to play an important role in the pathophysiology of at least part of the lower-risk myelodysplastic syndrome (MDS), the immunomodulating drug (IMID) thalidomide and its derivative lenalidomide (LEN) have been used in MDS, principally in lower-risk MDS. LEN has become the first-line US Food and Drug Administration (FDA)-approved treatment for lower-risk MDS with 5q deletion (del5q), in which its main mechanism of action is probably a direct cytotoxic activity on the del5q … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…There was no association between lenalidomide-induced cytopenias and achievement of responses, although this evaluation was difficult due to high rates of baseline cytopenias. Based on these results, Ades et al [78,79] suggested that the direct cytotoxicity of lenalidomide to the neoplastic 5q– clone in patients with LR-MDS can also been in patients with this clone and excess blasts. A 36% overall response rate (ORR) was reported in a prospective evaluation of 11 patients with IPSS HR-MDS and 5q– using higher doses of lenalidomide (30 mg daily) [80].…”
Section: Treatment Of Lr-mdsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no association between lenalidomide-induced cytopenias and achievement of responses, although this evaluation was difficult due to high rates of baseline cytopenias. Based on these results, Ades et al [78,79] suggested that the direct cytotoxicity of lenalidomide to the neoplastic 5q– clone in patients with LR-MDS can also been in patients with this clone and excess blasts. A 36% overall response rate (ORR) was reported in a prospective evaluation of 11 patients with IPSS HR-MDS and 5q– using higher doses of lenalidomide (30 mg daily) [80].…”
Section: Treatment Of Lr-mdsmentioning
confidence: 99%
“…In a recent study, low levels of RPS14 expression in patients with LR-MDS without 5q– were associated with higher rates of apoptosis erythroid progenitors and predicted better survival and possible response to lenalidomide [87]. It has been suggested that lenalidomide may also exhibit direct cytotoxic effects on the neoplastic clone in patients with HR-MDS and isolated 5q– as well [69,78,79,88]. …”
Section: Treatment Of Lr-mdsmentioning
confidence: 99%
“…The drug affects both cellular and humoral immunity,12 and has also been shown to have antiangiogenic properties, which stops the formation of new blood vessels and subsequently, decreases the blood supply to cause tumour regression 13. A crucial component of many of the anti-inflammatory properties of lenalidomide is its ability to suppress expression of TNF-α by affecting TNF signal transduction 14.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, the Kaelin and Ebert groups discovered that phthalimides (thalidomide, lenalidomide, and pomalidomide) induced the degradation of the lymphoid transcription factors Ikaros Family Zinc Finger 1 and 3 (IKZF1 and IKZF3) 152154 by binding to CRBN (K d = 150–250nM) 155 and repurposing the E3 ligase to ubiquitinate the transcription factors. Further studies have found that not all of the phthalimides have the same substrate degradation spectrum and thus are utilized in different clinical situations: lenalidomide can induce the degradation of casein kinase Iα (CKIα); in contrast, thalidomide and pomalidomide are incapable of inducing CKIα degradation 156158 . Recently, screening for CRBN ligands that degraded other targets led to the identification of CC-885, a phthalimide derivative that targets G1 to S phase transition protein 1 homologue (GSPT1; also known as ERF3A) 159 .…”
Section: ) Proteolysis-targeting Chimeras (Protacs)mentioning
confidence: 99%